REVITALIZATION AND RECOVERY OF ORIGINAL LANGUAGES: THE TUPINAMBÁ CASE, OLIVENÇA (BAHIA) - Santos, Clara Carolina Souza (2020)
In this text, we will present the choices for a Tupinambá spelling, elected in a democratic and enlightened assembly, which took place in 2010, with indigenous leaders and teachers, in the Tupinambá community, Olivença - Bahia. This linguistic assistance was requested by the Tupinambá community itself, which was obliged to accept the Portuguese language in its social interactions, after a long process of conflict and oppression. The linguistic recovery and revitalization in a community seeks to insert elements of the original language in indigenous schools, teaching the target language (Tupinambá) in biweekly meetings, aimed at the production of didactic material for school use.